RNA-Seq reveals complex genetic response to deepwater horizon oil release in Fundulus grandis - Garcia, Tzintzuni I; Shen, Yingjia; Crawford, Douglas; Oleksiak, Marjorie F; Whitehead, Andrew; Walter, Ronald B (BMC genomics, 2012)
Background The release of oil resulting from the blowout of the Deepwater Horizon (DH) drilling platform was one of the largest in history discharging more than 189 million gallons of oil and subject to widespread application of oil dispersants. This event impacted a wide range of ecological habitats with a complex mix of pollutants whose biological impact is still not yet fully understood. To better understand the effects on a vertebrate genome, we studied gene expression in the salt marsh minnow Fundulus grandis , which is local to the northern coast of the Gulf of Mexico and is a sister species of the ecotoxicological model Fundulus heteroclitus . To assess genomic changes, we quantified mRNA expression using high throughput sequencing technologies (RNA-Seq) in F. grandis populations in the marshes and estuaries impacted by DH oil release. This application of RNA-Seq to a non-model, wild, and ecologically significant organism is an important evaluation of the technology to quickly assess similar events in the future. Results Our de novo assembly of RNA-Seq data produced a large set of sequences which included many duplicates and fragments. In many cases several of these could be associated with a common reference sequence using blast to query a reference database. This reduced the set of significant genes to 1,070 down-regulated and 1,251 up-regulated genes. These genes indicate a broad and complex genomic response to DH oil exposure including the expected AHR -mediated response and CYP genes. In addition a response to hypoxic conditions and an immune response are also indicated. Several genes in the choriogenin family were down-regulated in the exposed group; a response that is consistent with AH exposure. These analyses are in agreement with oligonucleotide-based microarray analyses, and describe only a subset of significant genes with aberrant regulation in the exposed set. Conclusion RNA-Seq may be successfully applied to feral and extremely polymorphic organisms that do not have an underlying genome sequence assembly to address timely environmental problems. Additionally, the observed changes in a large set of transcript expression levels are indicative of a complex response to the varied petroleum components to which the fish were exposed.